PowerPoint in accounting classrooms: constructive or destructive? - El Khoury, Rim (2012)
This research investigated the impact of two teaching methodologies, PowerPoint and traditional, on materials’ understandability, the teaching/learning process, the students’ attitude towards and preference for them, as well as their impact on students’ performance in the Financial Accounting II course at XYZ University, in Lebanon. A self-completion questionnaire was distributed to 428 students. SPSS was employed to code the data and analyze it using the factor analysis and the Independent T-test. Results reflected a greater material understandability and a more effective teaching/learning process for the lectures explained with the traditional methodology versus PPT. However, no difference was found in students’ attitude towards the two teaching methodologies in terms of entertainment and dullness. Furthermore, students stated their preference for the traditional methodology in accounting courses. Finally, an ordinary least regression with the students’ grade as the dependent variable shows that PPT negatively affects students’ performance. Overall, the results suggest a convergence between the students’ subjective and objective performance.